Hybrid De-embedding Technique for Microwave Absorber Characterization - Achmad Munir (Universitas Ahmad Dahlan, 2011)
In this paper, a data processing technique to obtain the true characteristic of microwave absorber material characterization is proposed. This technique addressed to overcome the limitations of port extension is known as hybrid de-embedding technique, which in principle is carried out by combining the structure model data of test fixture that is used with simulated data or experimental measurements. In this technique, the test fixture is simulated numerically to get S (scattering) parameter data. Then the S parameter is converted into the T parameter (transfer) to be used for de-embedding process by removing the characteristic of test fixture used so that the true characteristics of a microwave absorber material can be revealed. To verify the accuracy of technique proposed, the characteristics of a microwave absorber is simulated numerically and measured experimentally. The simulation and measurements results are then processed using the proposed technique to be compared with its ideal model. In general, the result of de-embedding process shows that the proposed technique has high accuracy.